The effects of an external equine nasal strip on thermoregulation during exercise - Buchalski, F. M.; Rankins, E. M.; Malinowski, K.; McKeever, K. H. (Journal of Equine Veterinary Science, 2022)
The purpose of this study was to examine the effects of an external nasal strip on thermoregulation during submaximal exercise in Standardbred horses. While several studies have been conducted to determine the effects of the external nasal strip on airway resistance, exercise induced pulmonary hemorrhage, gas exchange, and time to fatigue in maximally exercising horses, the effects of the nasal strip on equine thermoregulation have not yet been examined. It was hypothesized that the application of an external nasal strip would alter central venous temperature (Tcore), skin temperature (Tskin), and exercise time to reach a central venous temperature of 40 °C. Eight mature Standardbred horses each performed two submaximal exercise trials, one with a nasal strip (NS), and one without (control), on a high-speed equine treadmill with exercise concluding upon Tcore reaching 40 °C. There were no significant differences in Tcore or Tskin between the NS and control groups during pre-exercise, exercise or recovery (P > .05), nor were there differences (P > .05) in exercise time to reach a Tcore of 40 °C (NS: 11.8 ± 1.5 minutes; Control: 11.5 ± 1.1 min). We conclude that the application of an external nasal strip does not affect the equine thermoregulatory response during submaximal exercise.